RANCANG BANGUN SISTEM PENGAMAN PINTU BERBASIS INTERNET OF THINGS (IoT) - Nurlinah Nurdin; Heliawati Hamrul; Musyrifah Musyrifah (J-ICON : Jurnal Komputer dan Informatika, 2022)
The development of the internet of things (IoT) is one of the influencing factors in the industrial era 4.0 towards the next industrial era, where with this technology humans can communicate with electronic devices connected to microcontrollers remotely using an internet connection. The door is a place to enter or exit to start daily activities. Therefore, door security is the main thing in designing a good room security. This research uses research and development methods, namely methods that aim to produce or develop certain products. There are several stages in the research, namely (1) literature review (2) analysis of tool and material requirements (3) Arduino Integrated Development Environment (IDE) schema design (4) system design with Arduino Nano and (5) system testing and analysis. It can be concluded from the test results that the door safety device can work according to the design made, considering the results of the Arduino Uno which can be connected to Radio Frequency Identification (RFID) and read e-KTP ID and passive infra-red or PIR sensors to detect movement and send notification to Telegram.